Aplikasi mikrokapsul ekstrak kulit melinjo merah (Gnetum gnemon L.) pada minuman serbuk effervescent - Siregar, Tagor; Gunawan, Cindy (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Red melinjo (Gnetum gnemon L.) peels have high carotenoid content and have the potential to be a natural food colorant. But it is difficult to dissolve in water, easily degraded by heat, and light. Microencapsulation is the process of coating core material which is easily damaged by using coating material. The purpose of this research is to protect, maintain, and improve the stability and solubility of carotenoid from red melinjo skin extracts. This research consist of two stages, preliminary and main research. In the first stage preliminary research, red melinjo peels were extracted using ethyl acetate and its characteristics were analyzed. In the second stage preliminary research, microencapsulation of extract using spray drying method, then its characteristics were analyzed. In the main research, the determination of the number of microcapsules and the ratio of citric acid and tartaric acid based on the characteristics of the best effervescent powder drink. Characteristics of red melinjo peels extract, water content 18.47%, yield 1.37%, total carotenoid 19.41 mg/g sample, total phenolic 27.86 mg GAE/g sample, and total flavonoid 30.60 mg QE/g sample. Characteristics of microcapsules, encapsulation efficiency 62.10%, solubility of microcapsule 93.44%, total carotenoid 0.29 mg/g sample, total phenolic 1.2 mg GAE/g sample, and total flavonoid 2.23 mg QE/g sample, moisture content 6.18%, yield 65.72%, and vitamin C content 404.37 mg/100g. Selected effervescent powder drink with the treatment of 0.5 gram microcapsules and 1: 2 acid ratio has the highest total carotenoid content, which is 0.05 mg/g sample, pH 6.03, foam volume 129.17 ml, soluble time 156.17 second, water content 8.99%, and the color is red based on °Hue 29.08. The chemical composition are water content 8.99%, ash content 21%, protein content 0.06%, carbohydrate content 69.79%, fat content 0.16%, and vitamin C content of 2.35 mg/100ml.